Origin of cystic artery from hepatic artery proper and its surgical implications - Patil, Sachin; Rana, Kumkum; Kakar, Smita; Mittal, Anilkumar (International Journal of Research in Medical Sciences, 2017)
Cystic artery is usually a branch of right hepatic artery given in the Calot’s triangle. Variations in the origin of cystic artery have been reported but there is paucity of literature regarding these in Indian subjects. The present case describes the origin of cystic artery from the hepatic artery proper, with an unusual course, which was detected during routine cadaveric dissection. The development of biliary vasculature is quite complex and it accounts for many variations. Knowledge of cystic artery variability facilitates intraoperative identification of vessels in both classical and laparoscopic surgery of the bile ducts. This emphasises the importance of a thorough knowledge of the cystic arterial variations that often occur and may be encountered during both laparoscopic and open cholecystectomy. Uncontrolled bleeding from the cystic artery and its branches is a serious problem that may increase the risk of intraoperative lesions to vital vascular and biliary structures during hepatobiliary surgery.